Evolution of hypervirulence in carbapenem-resistant Klebsiella pneumoniae in China: a multicentre, molecular epidemiological analysis - Zhang, Yawei; Jin, Longyang; Ouyang, Pengwen; Wang, Qi; Wang, Ruobing; Wang, Juan; Gao, Hua; Wang, Xiaojuan; Wang, Hui (Journal of antimicrobial chemotherapy, 2020)
Abstract Objectives Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) have been increasingly reported in China. Here, a multicentre, longitudinal surveillance study on CR-hvKP is described. Methods We retrospectively investigated carbapenem-resistant K. pneumoniae (CRKP) in 56 centres across China during 2015–17 and screened the virulence genes (iucA, iroN, rmpA and rmpA2) for the presence of virulence plasmids. Hypermucoviscosity, serum killing and Galleria mellonella lethality experiments were conducted to identify CR-hvKP among strains with all four virulence genes. Capsule typing, fitness and plasmid features of CR-hvKP were also investigated. Results A total of 1052 CRKP were collected. Among these, 34.2% (360/1052) carried virulence genes and 72 of them had all four of the virulence genes tested. Fifty-five (76.4%) were considered to be CR-hvKP using the G. mellonella infection model, with KPC-2-producing K64-ST11 being the most common type (80%, 44/55). Prevalence of CR-hvKP differed greatly between regions, with the highest in Henan (25.4%, 17/67) and Shandong (25.8%, 25/97). A significant increase in CR-hvKP among KPC-2-producing ST11 strains was observed, from 2.1% (3/141) in 2015 to 7.0% (23/329) in 2017 (P=0.045). Alarmingly, compared with classic CRKP, no difference in growth was found among CR-hvKP (P=0.7028), suggesting a potential risk for dissemination. The hybrid virulence and resistance-encoding plasmid evolved from pLVPK and the resistance plasmid harbouring blaKPC-2, indicating evolution existed between the hypervirulence and hyper-resistance plasmid. Conclusions CR-hvKP were more frequently detected than previously assumed, especially among KPC-2-producing ST11. Dissemination of hypervirulence could be extremely rapid due to limited fitness cost. Also, the evolution of resistance genes into hypervirulence plasmids was identified, presenting significant challenges for public health and infection control.